Mardatilah Values and Islamic Ethical Governance: A Conceptual Framework for Measuring Civil Servant Work Integrity in Muslim-Majority Public Sectors - Endang Sarwiningsih; Emiliana Pudjiarti (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
This study develops and empirically tests the Mardatilah Curiosity Motivation model as an Islamic value-based governance framework for enhancing sustainable performance among civil servants in Muslim-majority public sectors. Mardatilah, derived from Arabic al-marḍāh (المرضاة) meaning "seeking Allah's pleasure," is integrated with curiosity motivation theory to construct a spiritually grounded intrinsic motivation framework applicable to public organizations. A quantitative design was employed involving 274 civil servants selected via stratified random sampling, with data analyzed using Structural Equation Modeling with AMOS 24.0. The model demonstrated acceptable fit (GFI = 0.918; CFI = 0.991; RMSEA = 0.020). Mardatilah Curiosity Motivation exerted the strongest influence on Civil Servant Sustainable Performance (β = 0.425, p < 0.001), exceeding the effect of Workplace Agility (β = 0.325, p < 0.001). At the same time, Ethical Work Climate significantly predicted both Workplace Agility (β = 0.338, p < 0.001) and Mardatilah Curiosity Motivation (β = 0.268, p < 0.001). These findings advance Islamic Organizational Theory by demonstrating that spiritually grounded motivation is an empirically measurable predictor of sustainable public-sector performance and offer a culturally responsive governance model for Muslim-majority bureaucracies.